Symposium on economic development - O Nuallain, Labhras; Black, R. D. Collison; Thompson, S. F.; Nevin, Donal; O'Keefe, P. (Statistical and Social Inquiry Society of Ireland, 1959)
I must, at the outset, congratulate Mr. Whitaker on succeeding, where others have failed, in arousing the authorities, both Governmental and Departmental, to the urgent necessity for a systematic programme of economic development and the importance of forward thinking in the formulation of financial and economic policies. One can only hope that the publication of ?Economic Development? will meet with a similar measure of success among those that control or direct the banking, commercial, industrial and agricultural activities of the nation.
Read before the Society, 1 May 1959
Keywords: Economic development; Irish economic growth; T. K. Whitaker; 314.15